Problem-solving and thinking skills resources for able and talented children - 344602 Teare, Barry (London : Network Continuum Education, 2006)
Annotation With curriculum links across a range of subjects, this book is intended for use in normal lessons, enrichment activities, for homework, on thinking skills courses, as competitions or as activities for extracurricular clubs or societies. Written with busy